Weight loss practices in Taekwondo athletes of different competitive levels - Ferreira da Silva Santos, J.; Takito, M. Y.; Artioli, G. G.; Franchini, E. (Journal of Exercise Rehabilitation, 2016)
This study investigated the prevalence, magnitude, and methods of rap-id weight loss among male and female Taekwondo athletes from all competitive levels. A questionnaire was administered to 72 men (regional/state level, n=31; national/international level, n=41) and 44 women (regional/state level, n=9; national/international, n=35). Among the male athletes, 77.4% of the regional/state level and 75.6% of the national/international athletes declared to have reduced weight to compete in lighter weight categories. Among women, 88.9% of regional/state level and 88.6% of national/international level reported the use of rapid weight loss strategies. Athletes reported to usually lose ~3% of their body weight, with some athletes reaching ~7% of their body weight. The methods used to achieve weight loss are potentially dangerous to health and no difference between sexes was found. Four methods were more frequently used by men athletes in higher competitive levels as compared to lower levels, as follows: skipping meals (Z=2.28, P=0.023, (2)=0.21), fasting (Z=2.337, P=0.019, (2)=0.22), restricting fluids (Z=2.633, P=0.009, (2)=0.24) and spitting (Z=2.363, P=0.018, (2)=0.22). Taekwondo athletes lost ~3% of their body mass, using methods potentially dangerous for their health. Although no difference was found between sexes, lower level athletes more frequently used methods such as skipping meals, fasting, restricting fluids and spitting. Considering that these health-threating methods are more commonly used by lower level athletes, specific education programs should be directed to them.